Transferrin receptor-targeted immunostimulant for photodynamic immunotherapy against metastatic tumors through β-catenin/CREB interruption - Mengyi Yan; Xiayun Chen; Xiaotong Li; Qianqian Liu; Baixue Yu; Yi Cen; Wei Zhang; Yibin Liu; Xinxuan Li; Ying Chen; Tao Wang; Shiying Li (Elsevier, 2024)
The immunosuppressive phenotype of tumor cells extensively attenuates the immune activation effects of traditional treatments. In this work, a transferrin receptor (TfR) targeted immunostimulant (PTI) is fabricated for photodynamic immunotherapy against metastatic tumors by interrupting β-catenin signal pathway. To synthesize PTI, the photosensitizer conjugated TfR targeting peptide moiety (Palmitic-K(PpIX)-HAIYPRH) is unitized to encapsulate the transcription interrupter of ICG-001. On the one hand, the recognition of PTI and TfR can promote drug delivery into tumor cells to destruct primary tumors through photodynamic therapy and initiate an immunogenic cell death with the release of tumor-associated antigens. On the other hand, PTI will interrupt the binding between β-catenin and cAMP response element-binding protein (CREB), regulating the gene transcription to downregulate programmed death ligand 1 (PD-L1) while upregulating C-C motif chemokine ligand 4 (CCL4). Furthermore, the elevated CCL4 can recruit the dendritic cells to present tumor-specific antigens and promote T cells activation and infiltration, and the downregulated PD-L1 can avoid the immune evasion of tumor cells and activate systemic anti-tumor immunity to eradicate lung metastasis. This work may inspire the development of antibody antibody-free strategy to activate systemic immune response in consideration of immunosuppressive conditions.